SFP-based vertical handover with MIH services for integrated Wi-Fi and WIMAX networks. (18th February 2020) - Litake, Shilpa; Mukherji, Prachi
The seamless vertical handover among different wireless systems are required to offer high quality services. It is attained by the developing standard IEEE 802.21 media independent handover (MIH) services. In this paper, single AP scanning, fast ranging and preregistration (SFP) approach is used in which the target AP is chosen based on the proposed idle capacity and signal strength with hybrid PS-GS algorithm. After selecting the target base station (BS), the handover decision algorithm based on SINR enabled with utilising RSSI, available bandwidth and monetary cost. In the proposed vertical handover scenario, the MAC overhead is minimised by reducing the scanning time. The efficiency of the proposed approach is evaluated in terms of scanning time, handover interruption time, handover latency, packet loss, packet delay and throughput. When compared with the existing handover procedures, better results obtained in the proposed handover procedure. The outcomes demonstrate that the hybrid algorithm retains a maximum capacity to escape from local optimums with faster convergence than the standard PSO and GSA.